Ultrahigh‐throughput screening system for directed polymer binding peptide evolution. Issue 8 (3rd May 2019) - Apitius, Lina; Rübsam, Kristin; Jakesch, Christina; Jakob, Felix; Schwaneberg, Ulrich
Abstract: Accumulation of plastics in the environment became a geological indicator of the Anthropocene era. An effective reduction of long‐lasting plastics requires a treatment with micro‐organisms that release polymer‐degrading enzymes. Polymer binding peptides function as adhesion promoters and enable a targeted binding of whole cells to polymer surfaces. An esterase A‐based Escherichia coli cell surface display screening system was developed, that enabled directed evolution of polymer binding peptides for improved binding strength to polymers. The E. coli cell surface screening system facilitates an enrichment of improved binding peptides from a culture broth through immobilization of whole cells on polymer beads. The polypropylene (PP)‐binding peptide liquid chromatography peak I (LCI) was simultaneously saturated at five positions (Y29, D31, G35, E42, and D45; 3.2 million variants) and screened for improved PP‐binding in the presence of the anionic surfactant sodium dodecylbenzenesulfonate (LAS; 0.25 mM). The cell surface system enabled efficient screening of the generated LCI diversity (in total ~10 million clones were screened). Characterization of identified LCI binders revealed an up to 12‐fold improvement (eGFP‐LCI‐CSD‐3: E42V/D45H) in PP‐binding strength in the presence of the surfactant LAS (0.125 mM). The latter represents a first whole cell display screening system to improve adhesion peptides which can be used to direct and to immobilize organisms specifically to polymer surfaces (e.g., PP) and novel applications (e.g., in targeted plastic degradation). Abstract : An esterase A‐based ultrahigh‐throughput screening system allows the presentation of engineered anchor peptides on the Escherichia coli cell surface. In a directed evolution campaign, the polypropylene (PP)‐binding peptide LCI was simultaneously saturated at five positions and screened for improved PP‐binding. Improved binding variants immobilized whole E. coli cells on PP beads and were enriched from a culture broth. An identified LCI variant showed 12‐fold improved PP‐binding strength in comparison to the LCI wild‐type in the presence of the anionic surfactant LAS.